2013
DOI: 10.1073/pnas.1303289110
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of SecYEG in the active translocase of Escherichia coli varies with precursor species

Abstract: We have established a reconstitution system for the translocon SecYEG in proteoliposomes in which 55% of the accessible translocons are active. This level corresponds to the fraction of translocons that are active in vitro when assessed in their native environment of cytoplasmic membrane vesicles. Assays using these robust reconstituted proteoliposomes and cytoplasmic membrane vesicles have revealed that the number of SecYEG units involved in an active translocase depends on the precursor undergoing transfer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 45 publications
6
79
0
Order By: Relevance
“…These observations suggest that the bacteria rearrange translocon composition and/or stoichiometry in order to adapt to the hypersecretion state during infection. In this regard it was shown recently that the translocon stoichiometry varies upon translocation of different precursors, for example, outer membrane versus periplasmic protein (49). In light of these findings and the numerous reports that the SecYEG translocon can be found in various types of oligomers (50)(51)(52), it is tempting to speculate that bacteria modify the composition and/or the stoichiometry of the translocon apparatuses as a mechanism to cope with different secretion/translocation requirements.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the bacteria rearrange translocon composition and/or stoichiometry in order to adapt to the hypersecretion state during infection. In this regard it was shown recently that the translocon stoichiometry varies upon translocation of different precursors, for example, outer membrane versus periplasmic protein (49). In light of these findings and the numerous reports that the SecYEG translocon can be found in various types of oligomers (50)(51)(52), it is tempting to speculate that bacteria modify the composition and/or the stoichiometry of the translocon apparatuses as a mechanism to cope with different secretion/translocation requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, dimerization allows SecYEG to transit from a resting state to a translocation-ready state, characterized by greater SecA binding affinity (20) and more flexibility of the plug domain to accommodate preprotein (10). Interestingly, a recent study hints at a more subtle type of dimer function where the nature of the preprotein substrate may determine whether transport occurs via a SecYEG monomer or dimer (31). This phenomenon points to a possible structural signal within particular substrate proteins that facilitates dimer formation.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also functionally disrupted SecY dimer assembly by mutagenesis at the dimer interface, further supporting the functional monomer view. Adding to the ongoing controversy, a recent study utilizing a highly efficient SecYEG reconstitution system found that preproteins apparently differed in their translocon stoichiometry requirement, where a monomer or dimer was required depending on the preprotein species under study (31).…”
mentioning
confidence: 99%
“…The substitutions were made by standard recombinant DNA techniques (QuikChange, Stratagene). SecB and SecA were purified as described [14, 22]. 14 C –SecB was purified from a culture radiolabelled by growth in minimal medium (M9, vitamin B 1 , 0.4% glycerol).…”
Section: Methodsmentioning
confidence: 99%